Language's vanishing act in early literacy education. (February 2020) - Hruby, George G.
Current conversations about children's literacy have focused on the need for more phonics and decoding instruction and have sidelined the importance of children's language development, argues George Hruby. Language development involves more than the ability to decode written language. The ability to understand the meaning of those words is also important, and poor outcomes on reading assessments are not necessarily evidence of poor decoding skills. Hruby posits that comprehension follows a recursive trajectory that he calls ELIK in which students' linguistic environment affects their language abilities which affects their intellectual growth, which affects their knowledge. Against this backdrop, a lack of attention to linguistic environment is an issue of equity, with children who grow up in less literacy-rich environments coming into school at a disadvantage .